Embrace Indonesia: a Collaborative Digital Platform Between Creative Industry Actors and Non-Governmental Organizations - Fauzan Firdaus Risya; Lokita Rizky Megawati; Popong Nurhayati (Business Review and Case Studies, 2022)
Indonesia’s economic growth had shown a positive trend in the span of 2015-2020. On the other hand, Indonesia’s economic growth affected the inequality in a negative way. Ideally, the economic growth must be followed by social development actions. Researcher designed a digital platform which was formed as a combination of marketplace and crowdfunding model. This research aimed (1) to analyze consumer interests and problems in shopping and donating online (2) to formulate appropriate features and services to answer consumer interests and problems in shopping and donating online, (3) to develop verified business models and to design Embrace Indonesia prototypes according to consumer preferences. This research was conducted based on the stages of customer discovery in the customer development method to identify problems and generate business models to be a solution to the problem of shopping and donating online. The results of the research identifed 10 problems and their solutions in shopping and donating online by providing 6 features on the prototype, as well as a verified business model for Embrace Indonesia. The results of found that Embrace Indonesia's features as a digital platform can be a solution for customers in shopping and donating online. Keywords: inequality, digital platform, business model canvas, marketplace, crowdfunding